Biochemical content in roselle var UMKL-1 calyx cultivated under different soil media - Tan Wei Hsiang; Nur Ashira Azmin; Destinnie Anne Degullacion; Siti Aishah Mohd Ali (Faculty of Science & Natural Resources, UMS, 2024)
This work aimed to investigate the biochemical constituents’ (total anthocyanin content (TAC), total phenolic content (TPC) and antioxidant activity using DPPH assay) in the roselle UMKL1 calyces cultivated in different types of soil (ultrabasic, clay and organic soils). TPC results indicated that roselle UMKL-1 calyces cultivated in clay soil exhibited the highest value at 8.54 ± 3.32 mg GAE/g DW, with the lowest in organic soil at 3.06 ± 0.69 mg GAE/g DW. In terms of TAC, roselle UMKL-1 grown in organic soil recorded the highest value at 2.91 ± 0.72 mgC3G/gDW, while the lowest was in clay soil at 1.83 ± 0.43 mgC3G/gDW. Antioxidant activity expressed as IC50 (mg/mL), showed the lowest value in clay soil (0.257 ± 0.008 mg/mL). One-way ANOVA indicated significant variation between soil media treatments only for TPC (p < 0.05). In general, roselle UMKL-1 calyces cultivated in clay soil media may produce better total phenolic content and antioxidant activity.